Hubungan Pelaksanaan Shalat 5 Waktu dengan Quality Of Life pada Mahasiswa di Semarang - Laily Nafisah; Wigyo Susanto; Dwi Heppy Rochmawati (Jurnal Anestesi, 2025)
A number of students often put aside prayer because of the demands of assignments or work that they consider cannot be abandoned. This can result in prolonged stress and poor self-control. Performing prayer can make it easier to resolve various matters, including overcoming work challenges. Prayer has a horizontal function that can renew human qualities and personality. This research aims to determine the relationship between performing the 5 daily prayers and the quality of life of students. This research is a cross sectional study. The data used in this research was obtained from direct questionnaires by respondents. The sample used in this research was 59 respondents. The sampling technique is total sampling. Research data analysis used univariate and bivariate tests, bivariate analysis used the chi-square test. The results of the univariate analysis of the 5th prayer at most times were sometimes with 28 people with a percentage of (47.5%). The highest quality of life was moderate with 29 percentages (49.2%). The highest data of respondents with female gender was 48 students with a percentage of (81.4%). The largest number of respondents was 20 years old with a total of 34 students with a percentage of (57.6%). The results of bivariate analysis with the chi-square test show that there is a relationship between the 5 daily prayers and quality of life with a p value of 0,000, this value is <0,005.